Chemical Composition, Antioxidative and Cholesterol Lowering Properties of Selected Malaysia Seaweeds - Matanjun, Patricia (2008)
The objectives of this study were to evaluate in vitro antioxidant activity and total phenolic screenings of eight species of Malaysia seaweeds (Kappaphycus alvarezii, Eucheuma denticulatum, Halymenia durvillaei, Caulerpa lentillifera, Caulerpa racemosa, Dicyota dichotoma, Sargassum polycystum and Padina spp.), determine chemical composition of three selected edible seaweeds and investigate effects of these seaweeds on antioxidative, cholesterol-lowering, and their effects on biochemical, morphological and histological characteristics of selected tissues of rats fed on high-cholesterol/high-fat (HCF) diets. In vitro antioxidant activities of the eight species of seaweeds were evaluated using TEAC (trolox equivalent antioxidant capacity) and FRAP (ferric reducing antioxidant power) assays. Total phenolic contents of these seaweeds were determined using Folin-Ciocalteu assay. Red seaweed K. alvarezii, green seaweed C. lentillifera and brown seaweed S. polycystum were selected based on their high in vitro antioxidant activity, and further evaluated for their chemical composition, in vivo antioxidant activity and cholesterol-lowering effects in Sprague Dawley rats fed with HCF diet for 16 weeks. Chemical analysis of seaweeds comprised of proximate composition, dietary fiber, vitamin C, vitamin E (α-tocopherol), minerals, carotenoids, chlorophylls, fatty acids and amino acids. Animal experimental diets comprised of eight groups: normal diet (N, control group), HCF diet (HCF group), normal diet supplemented with 5% seaweeds (N+KA, N+CL and N+SP groups), and HCF diet supplemented with 5% seaweed (HCF+KA, HCF+CL and HCF+SP groups). Effects of seaweeds in preventing hypercholesterolaemia and peroxidation in rats were studied via assessing the plasma lipids and, plasma and organs malondialdehyde (MDA) concentrations. Likewise, activities of antioxidant enzymes such as superoxide dismutase (SOD), glutathione peroxidase (GSH-Px) and catalase (CAT) were accessed as indices of oxidative stress. Biochemical markers for liver, heart and kidney damage such as alanine aminotransferase (ALT), aspartate aminotransferase (AST), γ-glutamyltransferase (GGT), creatinine kinase (CK), CK-MB isoenzyme, urea, creatinine and uric acid were measured. Somatic index and descriptive histological changes in the liver, heart, kidney, brain, spleen and eye of the experimental rats were also performed, while quantitative histology was restricted only to necrosis in the liver, kidney and brain. The results showed that administration of K. alvarezii and C. lentillifera reduced (P<0.05) plasma low-density lipoprotein cholesterol and triglyceride, and increased (P<0.05) plasma high-density lipoprotein cholesterol thus improving the atherogenic index of rats fed a HCF diet. These seaweeds were shown to reduce body weight gain in rats fed a HCF diet in the following order S. polycystum>C. lentillifera>K. alvarezii. However, K. alvarezii and C. lentillifera were more effective than S. polycystum in improving the antioxidant status by reducing (P<0.05) lipid peroxidation and increasing (P<0.05) antioxidant enzymes in liver, heart and kidney of rats fed the HCF diet. Histological examinations demonstrated consumption of all three seaweeds did not exert any damage to the liver, heart, kidney, brain, spleen and eyes in normal rats. In conclusion, K. alvarezii and C. lentillifera showed hypolipidaemic effects, improve antioxidant status and exert a protective effect in mitigating the cardiac, hepatic, renal and brain abnormalities in rats fed HCF diet. The presence of high dietary fiber especially soluble fiber, omega-3 fatty acids such as eicosapentaenoic acid (C20:5ω3), and antioxidant compounds such as polyphenols, vitamin C, α-tocopherol, carotenoids and selenium may probably contributed to the cholesterol-lowering and antioxidant efficacy of these seaweeds.